ANALISIS BAHAN AJAR PADA MATA KULIAH KALKULUS LANJUT - Nurul Farida; Rina Agustina (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2017)
Teaching materials are learning resources in the form of materials or materials arranged systematically to help educators in learning so that learners are able to master the competence to be achieved. Based on the results of prasurvey obtained results that not yet available teaching materials that are able to facilitate, find, and develop mathematical concepts in advanced calculus course. Inquiry is a learning activity that emphasizes the critical thinking process and analysis to find and solve the problems until get a conclusion.This study aims to analyze the process of preparing the teaching material based inqury in Advanced Calculus course. The results obtained from this study are the teaching material based inqury in Advanced Calculus course which received an average validation score of 63% in the eligible categories of language, instructional design, and materials, and it can be implementation in advanced calculus learning.